2017
DOI: 10.48550/arxiv.1704.06840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ranking with Fairness Constraints

Abstract: Ranking algorithms are deployed widely to order a set of items in applications such as search engines, news feeds, and recommendation systems. Recent studies, however, have shown that, left unchecked, the output of ranking algorithms can result in decreased diversity in the type of content presented, promote stereotypes, and polarize opinions. In order to address such issues, we study the following variant of the traditional ranking problem when, in addition, there are fairness or diversity constraints. Given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…(2018) and references therein. Our paper adds to the literature on fair methods for unsupervised learning tasks (Chierichetti et al, 2017;Celis et al, 2017;Samadi et al, 2018;Tantipongpipat et al, 2019;Oneto and Chiappa, 2020;Caton and Haas, 2020;Kleindessner et al, 2019). We discuss the work on fairness most closely related to our paper.…”
Section: Related Workmentioning
confidence: 81%
“…(2018) and references therein. Our paper adds to the literature on fair methods for unsupervised learning tasks (Chierichetti et al, 2017;Celis et al, 2017;Samadi et al, 2018;Tantipongpipat et al, 2019;Oneto and Chiappa, 2020;Caton and Haas, 2020;Kleindessner et al, 2019). We discuss the work on fairness most closely related to our paper.…”
Section: Related Workmentioning
confidence: 81%
“…To address this challenge, multiple notions of fairness in ranking have been developed. Celis et al [6] propose to directly require fair representation between groups within each prefix of a ranking, by specifying a mixed integer programming problem to solve for rankings of the desired form. Zehlike et al [22] design a greedy randomized algorithm to produce rankings which satisfy fairness up to a threshold of statistical significance.…”
Section: Related Workmentioning
confidence: 99%
“…The question of fairness in rankings originated from independent audits on recommender systems or search engines, which showed that results could exhibit bias against relevant social groups [57,33,21,40,35] Our work follows the subsequent work on ranking algorithms that promote fairness of exposure for individual or sensitive groups of items [10,8,7,54,42,65]. The goal is often to prevent winner-take-all effects, combat popularity bias [1] or promote smaller producers [39,41].…”
Section: Related Workmentioning
confidence: 99%